Managing local brands in facing challenges of globalization: Be a local or global leader? - Harun, Amran; Mohd Kassim, Abdul Wahid; Igau, Aizad Oswald; Hassan, Mohamad Ghozali; Swidi, Abdullah (College of Law, Government and International Studies, Universiti Utara Malaysia., 2010)
This article is resulting from literature review with in mind after taking into consideration all previous studies in regard to branding issue. All views and advice from academicians and practitioners are modified to fit with local issue. Domestic entrepreneurs are expected to be confronted by fierce competitions in the local markets after the arrival of regional free trade agreement in SEA countries also known as AFTA (Asean Free Trade Area). This situation further worsens by impact of globalization which indirectly influences their business performance. As entrepreneurs from developing country it is challenging to compete with global players that are well-established. Therefore, the discussion of this working paper concentrates on the issue of branding which guides local entrepreneurs to manage brand more effectively. Finally, the framework on strategic branding for local players will be discussed more detailed.